Flexible Nets for the Optimization of IgG Production in CHO cells - Lázaro Ibáñez, Jorge; Joven, Teresa (Jornada de Jóvenes Investigadores del I3A, 2025)
Antibody production using CHO cells is often inefficient due to trial-and-error approaches. To improve this, we developed a mathematical model based on Flexible Nets that integrates cell metabolism and bioreactor dynamics. This multi-scale modeling enables systematic, optimized design of antibody manufacturing, enhancing productivity while reducing time and cost.